2023
DOI: 10.3390/ma16124271
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of AgNPs in a Lignin Isocyanate Film: Characterization and Antimicrobial Properties

Abstract: Lignin isolated from agricultural residues is a promising alternative for petroleum-based polymers as feedstocks in development of antimicrobial materials. A polymer blend based on silver nanoparticles and lignin–toluene diisocyanate film (AgNPs–Lg–TDIs) was generated from organosolv lignin and silver nanoparticles (AgNPs). Lignin was isolated from Parthenium hysterophorus using acidified methanol and used to synthesize lignin capped silver nanoparticles. Lignin–toluene diisocyanate film (Lg–TDI) was prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 48 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…3, the XRD pattern of the Gr-AgNPs/LCF composites showed obvious sharp peaks at 38.2°, 44.2°, 64.3°, and 77.3°, corresponding to the characteristic absorption peaks at the (111), (200), (220), and (311) planes of the face centred cubic Ag phase (JCPDS No. 87-0720), respectively, 18,38,39 which strongly confirmed that AgNO 3 was successfully reduced to Ag in the composite films. A high-resolution spectrum of Ag 3d, as depicted in Fig.…”
Section: Resultsmentioning
confidence: 53%
“…3, the XRD pattern of the Gr-AgNPs/LCF composites showed obvious sharp peaks at 38.2°, 44.2°, 64.3°, and 77.3°, corresponding to the characteristic absorption peaks at the (111), (200), (220), and (311) planes of the face centred cubic Ag phase (JCPDS No. 87-0720), respectively, 18,38,39 which strongly confirmed that AgNO 3 was successfully reduced to Ag in the composite films. A high-resolution spectrum of Ag 3d, as depicted in Fig.…”
Section: Resultsmentioning
confidence: 53%